2013
DOI: 10.1111/1440-1681.12101
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐stem cell formation by non‐plateletRNA‐containing particle fusion

Abstract: 1. We found a group of non-platelet RNA-containing particles (NPRCP) in human umbilical cord blood. To understand the origin, characterization and differentiation of NPRCP, we examined cord blood-isolated NPRCP in vitro.2. The NPRCP range in size from < 1 to 5 μm, have a thin bilayer membrane and various morphological features, contain short RNA and microRNA and express octamer-binding transcription factor 4 (OCT4), sex-determining region Y 2 (SOX2) and DEAD box polypeptide 4 (DDX4). On coculture with nucleate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Because each of these structures produces and releases only one distinct spore-like cellular type or progenitors, we believe that the lineage of these progenitors has been predetermined when their tube-shaped structures or niches are built. Also, in our previous report of cultured hUCB (Kong et al, 2013a), we observed many small particles and similar fusiform structures that we termed "Non-platelet RNAcontaining particles (NPRCPs) and "particle fusion-derived non-nucleated cells (PFDNCs), respectively. The small particles could fuse with each other to form small cellular structures, and two or more particle-derived small cells could further fuse or engulf each other to become larger-sized Oct4-and Sox-2-positive pre-stem cells.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Because each of these structures produces and releases only one distinct spore-like cellular type or progenitors, we believe that the lineage of these progenitors has been predetermined when their tube-shaped structures or niches are built. Also, in our previous report of cultured hUCB (Kong et al, 2013a), we observed many small particles and similar fusiform structures that we termed "Non-platelet RNAcontaining particles (NPRCPs) and "particle fusion-derived non-nucleated cells (PFDNCs), respectively. The small particles could fuse with each other to form small cellular structures, and two or more particle-derived small cells could further fuse or engulf each other to become larger-sized Oct4-and Sox-2-positive pre-stem cells.…”
Section: Introductionmentioning
confidence: 69%
“…These cellular structures eventually develop into mesenchymal stem cells. In our previous study (Kong et al, 2013a), we described how the new Oct4 and Sox-2-positive stem cells are formed by the fusion of particles, the NPRCPs, in hUCB. Now we believe that NPRCPs are small fusiform structures, which is hard to distinguish from the circulating particles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations